Pengaruh Konseling pada Ibu Nifas terhadap Pemberian Kolostrum pada Bayi Baru Lahir - Nurma Ika Zuliyanti; Anggieta Febriana (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
Some of the factors that cause mothers not to provide colostrum for their babies, and the reasons for the low practice of exclusive breastfeeding in Kebumen Regency are the lack of knowledge of mothers about the benefits of colostrum for babies, and several wrong perceptions about colostrum, which is seen as dirty breast milk, so it is not should be given to babies. Objective To determine the effect of postpartum counseling on colostrum delivery to newborns at Permata Ibu Clinic, Prembun District, Kebumen Regency. The method used was using a pre-experimental design with a one group pretest posttest design. The population in the study was 34 people. The analysis in this research is univariate analysis and bivariate analysis. Results: 17 people (45.8%) gave colostrum to their babies before counseling. There were 28 postpartum mothers who gave colostrum to their babies after counseling (90.3%). Based on the normality test on the pretest and posttest, it was obtained p <0.05, indicating that the data were not distributed. Positive Rank of 11. Wilcoxon test obtained Z count of -3.317 with p = 0.001.